Inventories in a Competitive Environment - Bental, Benjamin; Eden, Benjamin (Journal of Political Economy, 1993)
Trade is sequential: Buyers arrive in batches, and each batch completes trade before the next arrives. Producers allocate the available supply among all potential batches of buyers. Inventories accumulate whenever a batch does not arrive. Shocks to cost and demand are serially independent. There is a stationary relationship between inventories and prices with the following properties. Larger beginning-of-period inventories tend to depress prices. Inventories are positively serially correlated. A unit increase in inventories reduces output by less than one unit. An increase in inventories leads to an increase in the price spread. Output tends to vary more than sales.